The Relationship between the Use of Edulearning and the Learning Outcomes of PAI and Ethics in Grade VIII Junior High School Students: Hubungan Penggunaan Edulearning dengan Hasil Belajar PAI dan Budi Pekerti pada Siswa SMP Kelas VIII - Hilmi, Fuad (Edukasi: Journal of Educational Research, 2024)
This study aims to explore the relationship between the use of Edulearning and learning outcomes of Islamic Religious Education (PAI) and Budi Pekerti for grade VIII students at SMP Mekar Arum. The background of the study is based on the importance of optimising the use of technology in character education, especially in the midst of implementation challenges such as low teacher understanding of technology, diverse student learning motivation, and limited infrastructure. Using a qualitative approach and correlational method, this study involved 206 students as subjects. Data showed that the average use of Edulearning reached a score of 3.8 (scale 1-5), while the average student learning outcome was 78.5 (scale 0-100). Findings showed that most students were in the ‘Good’ (46.6%) and ‘Very Good’ (22.3%) learning outcome categories, indicating the effectiveness of Edulearning in supporting learning outcomes. This research revealed that the effectiveness was influenced by students‘ motivation, teachers’ skills in using technology, as well as school infrastructure support. The implication of this research shows that Edulearning has a significant contribution in character-based learning, especially in improving material understanding and internalisation of religious and moral values. The original value of this research lies in its contribution in strengthening religious digital literacy at junior high school level, as well as emphasising the importance of synergy between educational technology and value education in the context of character education relevant to 21st century needs.